Impact of hyperglycaemia on cellular microenvironment and function of endometrium and uterine tube: scoping review focused on infertility in diabetic women - Jackuliak, Peter; Jankovský, Martin; Kovářová, Magdaléna; Voller, Jaroslav; Feitscherová, Claudia; Varga, Ivan (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDiabetes mellitus (DM) and associated comorbidities correspond to female infertility by many interrelated mechanisms. Yet most prior research focuses only on ovary dysfunction. Our work evaluates literature mechanisms of DM-induced uterine tube and endometrial dysfunction, corresponding impacts on female fertility, and potential evidence-based intervention targets.MethodsWe conducted a scoping review (mapping review) follows the Joanna Briggs Institute (Manual for Evidence Synthesis, 2020 version). After identifying the research questions, we conducted a comprehensive search across four electronic databases by entering the keyword “diabetes”, with a combination with other keywords as the uterus, endometrium, uterine/Fallopian tube, infertility and embryo implantation. We excluded manuscripts that address the issue of gestational diabetes. Most of these studies were in animals.ResultsThere is compelling evidence for connecting DM with uterine tube infertility via endometriosis, thyroid dysfunction, and susceptibility to infectious disease. DM damages the endometrium before pregnancy via glucose toxicity, lesions, excessive immune activity, and other mechanisms. DM also hinders endometrium receptivity and embryo–endometrium crosstalk, such as through disrupted endometrium glucose homeostasis. We also hypothesize how DM may affect the function of immune cells in uterine tube and uterus, including changes in the number and types of cells of innate and acquired immunity, disrupting immunological barrier in uterine tube, alterations in formation of neutrophil extracellular traps or polarization of macrophages.DiscussionWe discuss evidence for clinical practice in terms of glycaemic control, lifestyle modifications, and medical interventions. For example, there is currently substantial evidence from rodent models for using metformin for increase in endometrial thickness, number of stromal cells and blood vessels and restoration of normal endometrial architecture, and bariatric surgery for recruitment of protective immune cell types to the endometrium. We also briefly highlight the future prospects of stem cells, artificial intelligence, and other new approaches for managing DM-associated female infertility. Further studies are necessary for optimizing female reproductive outcomes.